Exocentricity yet again: A response to Nóbrega and Panagiotidis. (July 2022) - Bauer, Laurie
Abstract : In this reply to a paper by Nóbrega and Panagiotidis in Word Structure 13, I consider some of the remarks they make about exocentric compounds, and compare them with the generally accepted view of such structures. I conclude that their view of hyponymy seems to be unduly restrictive, that their use of empty heads leads to potential analyses which might not be considered useful, and that their suggested criteria for exocentricity lead to their restricting the notion of exocentricity in compounds to those which are marginal members of the exocentric category. I propose some lines for future research.